229k views
1 vote
I need help please????

I need help please????-example-1
User Rejeesh
by
4.7k points

2 Answers

6 votes

Answer:

x = - 1

Explanation:

Given

3x + 2 = y and y = - 1

Substitute y = - 1 into the equation and solve for x, that is

3x + 2 = - 1 ( subtract 2 from both sides )

3x = - 3 ( divide both sides by 3 )

x = - 1

This is verified by the point on the graph with coordinates (- 1, - 1)

User Sashi Kolli
by
4.5k points
3 votes

Method 1: By substitution

Step 1: In the equation 3x + 2 = y when you see a y replace it with -1

3x + 2 = -1

Step 2: Combine like terms by subtracting 2 to both sides

3x + (2-2) = -1 - 2

3x = -3

Step 3: Isolate x by dividing 3 to both sides


(3x)/(3) = (-3)/(3)

x = -1

Method 2: By looking at the graph

To solve this way you see where the line on the graph has y = -1 and look for its complimentary x

If you look at the graph attached below you can see that at y = -1 the x also equals -1

x = -1

Hope this helped!

I need help please????-example-1
User Daharon
by
4.8k points